An intracranial space occupying lesion in a 4-year-old child: a case report - E. S., Akshara; Nadkarni, Jayashree (International Journal of Contemporary Pediatrics, 2018)
Primary central nervous system tumours are a heterogenous group of diseases that are collectively, the second most common malignancy in childhood and adolescence. The overall mortality among this group approaches 30%. Despite of high mortality rates, outcomes of these malignancies has improved with neurosurgery, radiation therapy, and chemotherapy as a therapeutic modality. Here authors have reported a 4-year female child who was diagnosed with brainstem glioma in present institute. The child presented with the typical clinical presentations of brainstem glioma.